2007
DOI: 10.1007/s00109-007-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and the HIF system in kidney disease

Abstract: The kidney is sensitive to changes in oxygen delivery. This sensitivity has the merit of facilitating the kidneys in their adjustment of erythropoietin (EPO) production to changes in oxygen supply. The main determinant of EPO synthesis is the transcriptional activity of its gene in kidneys, which is related to local oxygen tensions. Regulation of EPO production is mediated by hypoxia-inducible factor (HIF). When local oxygen tension decreases, accumulated HIF binds to the key sequence of the EPO gene, the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
206
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(218 citation statements)
references
References 46 publications
6
206
0
6
Order By: Relevance
“…Decreased oxygen tension is the principal stimulus for renal Epo expression, yet Epo production decreases in CKD, which is associated with chronic hypoxia (33,34). When Epo production is impaired in the injured kidney, extrarenal sources of Epo cannot compensate for decreased Epo levels (35).…”
Section: Identification Of Renal Interstitial Fibroblasts As Primary mentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased oxygen tension is the principal stimulus for renal Epo expression, yet Epo production decreases in CKD, which is associated with chronic hypoxia (33,34). When Epo production is impaired in the injured kidney, extrarenal sources of Epo cannot compensate for decreased Epo levels (35).…”
Section: Identification Of Renal Interstitial Fibroblasts As Primary mentioning
confidence: 99%
“…The true value of understanding mechanisms that underlie control of Epo expression may be the possible therapeutic solutions to overcome the transcriptional silencing of Epo, a hallmark of CKD (47). While hypoxia is the principal stimulus for Epo expression under physiologic conditions, Epo transcription is silenced in chronically diseased kidneys, despite the hypoxic conditions that are a hallmark of renal fibrogenesis (34).…”
Section: Regulation Of Epo Productionmentioning
confidence: 99%
“…HIF-1 and HIF target genes such as EPO, VEGF, and GLUT-1 are upregulated as an adaptive response to hypoxia. [32][33][34] Previous studies have demonstrated that chemical preactivation of HIF protected renal IRI and induced upregulation of HIF-target genes. 35,36 Although HIF-1␣ expression was marginally enhanced by IRI or hypoxia only in our study, NKT activation by sulfatide increased HIF-1␣ expression significantly.…”
Section: Cd4mentioning
confidence: 99%
“…[71][72][73] Medullary hypoxia is an inevitable consequence of the unique architecture of the medullary vasculature that serves a countercurrent isolation function that prevents the medullary solute gradient from being dissipated and hence allows for urinary concentrating ability. 72,74,75 The antiparallel arrangement of blood vessels allows diffusional shunting of oxygen between descending arterial vasa recta and ascending venous vasa recta (countercurrent exchange). As a consequence, the oxygen tension in the renal outer medulla remains between 10 and 20 mmHg with even lower oxygen tensions in the inner medulla, whereas the cortex benefits from an oxygen tension between 30 and 50 mmHg.…”
Section: Oxygen Delivery To the Kidneymentioning
confidence: 99%